(untitled) (Research, Society and Development, 2022)
Bell’s palsy is the most common cause of unilateral facial palsy reported in the literature. This condition consists of causing rapid onset and unilateral peripheral paresis/paraesthesia of the seventh cranial nerve. Despite being well documented, its etiology is still uncertain, imposing difficulty in immediate treatment. The combination of laser therapy and ozone therapy was proposed as a new treatment method for Bell’s palsy, as it combines the efficacy and response of a therapy with the benefits of a minimally invasive approach. In the present study, we describe the first treatment protocol combining laser therapy and ozone therapy in Brazil, as well as details of the technique for the treatment of Bell’s palsy. Case Report: A 59-year-old female with paralysis and paresthesia in the right hemiface, diagnosed for Bell’s palsy, underwent a combined treatment of laser therapy and ozone therapy (VK OzonTherapy). After the fourth treatment session, a great clinical response was observed, and another session of the VK OzonTherapy protocol was performed. The patient evolved with significant improvement in the sequelae of right hemifacial paralysis, oro-ocular and eye closure, with rapid recovery of muscle tone and correction of asymmetries. Conclusions: This Report shows that the VK OzonTherapy protocol is an adjunct tool for clinical practice capable of improving the aesthetic-functional quality of life in patients with recent unilateral facial palsy.